DEKONSTRUKSI PERLAWANAN HEGEMONI DALAM FILM DOKUMENTER AMERICAN FACTORY - Kristianto, Bernard Realino Danu (LPPM Stikosa - AWS, 2024)
Capitalism permeates all cultural and ideological contexts of everyone, including those who consciously uphold the principles of socialism. A Chinese company called Fuyao, is a company engaged in the production of car glass on an international scale. In an effort to increase the company's production, Fuyao Glass America is immersed in the hegemony of capitalism in the midst of intercultural communication problems that actually become important issues and must be resolved internally in the factory. The context of capitalist hegemony along with ideological conflicts and intercultural communication is what the documentary American Factory depicts. Using Teun Van Dijk's critical discourse analysis, researcher wanted to look at the text, cognition and context as a whole that took place in the documentary. Researcher found in depth at the text manifested from dialogue, images, scenes and visualizations, the cognition manifested from the actors of filmmaking including the production house that houses its distribution, as well as the context of intercultural communication issues and ideological battles that exist in it. As a result of this study, the documentary American Factory is a representation of the Chinese version of capitalism presented through policies and doctrines to the workers of Fuyao Glass America company in an effort to increase company productivity and capital investment in the United States.